الرأي العام في الإسلام المحددات المعرفية والتنزيلات الواقعية في المرحلة المدنية - عي, سعد (My University, 2016)
يتناول البحث دراسة الرأي العام في الإسلام من الجانبين النظري والواقعي، وذلك من خلال فصلين، الفصل الأول: يتضمن المحددات المعرفية، أي الجانب النظري بدءا من بيان مفهوم الرأي العام مرورا بتوضيح نشأته وإبراز أهم ملامحه من القرآن والسنة وبعض مصادر التشريع، ثم الوقوف عند مقوماته وأهميته ودوره في المجتمع، كذا أهم عوامل تكوينه كالحرية والشورى والأمر بالمعروف والنهي عن المنكر، والأساليب التي اعتمدها الإسلام والتي نبذها في تشكيل الرأي العام، ثم ينتهي الفصل الأول ببيان أوجه الاتفاق وأوجه الاختلاف بين ال رأي العام في الإسلام والرأي العام في الأيديولوجيات الأخرى. أما الفصل الثاني فيتناول التنزيلات الواقعية للرأي العام الإسلامي في المرحلة المدنية، وذلك بمحاولة تتبع ملامحه من خلال بعض المحطات التاريخية في هذه المرحلة، كتسليط الضوء على بعض النماذج في مرحلة تأسيس المجتمع الإسلامي في المدينة المنورة، واختيار بعض الغزوات المهمة ودور الرأي العام فيها، كما تضمن موقف الرأي العام من بعض تصرفات اليهود والمنافقين، فضلا عن دورهفي جملة من الحوادث الأخرى المتفرقة This research deals with the study of ' public opinion in Islam ' from both theoretical and realistic sides, and that, through two chapters: The first chapter includes cognitive determinants, i.e. the theoretical side, starting from the statement of the concept of public opinion, and passing through clarifying its inception and highlighting the most important features of the Qur'an and Sunnah and some of the sources of legislation, and then, standing at its constituents , its importance and its role in the society, as well as the most important factors of its constituation such as freedom, Shura and the Promotion of Virtue and Prevention of Vice, and the methods adopted by Islam, which started discarded in shaping public opinion. Then, the first chapter ends with a statement on the agreement aspects and the differences between public opinion in Islam and public opinion in other ideologies. The second chapter deals with realism downloads of Islamic public opinion in the civil phase, and that by trying to keep track of the features through some historical stations at this stage, as focusing on some models in the establishment of the Islamic community in Medina stage, the choice of some important invasions and the role of public opinion, which, as public opinion of some Jews' and hypocrites' actions not included, as well as its role in a number of other sporadic incidents
ماستر دعوة
Keywords: الرأي العام,الإسلام,المحددات المعرفية,والتنزيلات الواقعية,المرحلة المدنية; Public opinion, Islam, cognitive determinants, realistic downloads, the civil stage